Study of clinical profile and risk factors associated with febrile urinary tract infection in preschool children - G. V., Kumar; George, Aaron; H. M., Viswanathakumar (International Journal of Contemporary Pediatrics, 2016)
Background: Urinary tract infection (UTI) is a term applied to a variety of clinical conditions ranging from asymptomatic presence of bacteria in the urine to severe infection of the kidney with resultant sepsis. According to The National Institute for Health and Clinical Excellence (NICE) guidelines, urinary tract infection is defined by a combination of clinical features and the presence of bacteria in urine. The risk factors of UTI are age, gender, constipation, lack of circumcision, not taking anthelmintic and lack of toilet training. Methods: This was across sectional study conducted on febrile preschool children, aged 3 to 6 years, who attended the outpatient department of Sri Siddhartha Medical College, Tumkur. Children with symptoms suggestive of UTI were enrolled, and a written informed consent was obtained from the parents. They were then interviewed using structured questionnaire for UTI. Results: Out of 194 febrile preschool children, 21 cases were diagnosed to have UTI. Of the 194 cases, 102 (52.6%) were females and 92 (47.42%) were male. Out of 21 urine culture positive cases 14 (66.6%) were females and 7 (33.33%) were males. Occurrence of UTI was 7.6% in febrile males, 13.72% in febrile females and had the estimated overall occurrence is 10.8%. Fever was present in all the cases. Besides fever, 47.62% children had increased frequency, 42.86% had excessive crying while micturition and 38.10% had chills and rigors. Foul smelling urine was present in 33.33% of children while 23.81% had abdominal pain. Out of 92 male children studied 16 (17.39%) males had phimosis, of which 2 (12.5%) developed urinary tract infections. Constipation was seen in 3 (14.29%) children with UTI. Worm infestation was seen in 5 (23.81%) children with UTI. Conclusions: Children with urinary tract infections usually present with nonspecific symptoms and signs and hence a urine analysis and culture should always be part of an initial diagnostic evaluation of urinary tract infections. Female sex, constipation, not taking anthelmintic, lack of toilet training and phimosis are significant risk factors for febrile urinary tract infection in children.